2019
DOI: 10.1186/s13046-019-1379-5
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA PXN-AS1 suppresses pancreatic cancer progression by acting as a competing endogenous RNA of miR-3064 to upregulate PIP4K2B expression

Abstract: Background Dysregulation of microRNAs (miRNAs) play critical roles in cancerous processes. Although miR-3064 was reported to be an important tumor suppressor in ovarian cancer, the cellular impact of miR-3064 on pancreatic cancer (PC) progression, its downstream target genes and upstream mechanisms that control the expression of miR-3064 remain to be fully clarified. Methods We compared miRNA expression profiles between PC tissues compared with normal tissues using a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 25 publications
(31 reference statements)
1
39
0
Order By: Relevance
“…Recent studies have indicated that lncRNAs played a key role in the progression of ovarian cancer. 16,17 In the present research, we confirmed that the expression of lncRNA-ATB was significantly upregulated in ovarian cancer cells. Li et al found that the expression of lncRNA GAS5 was notably inhibited in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have indicated that lncRNAs played a key role in the progression of ovarian cancer. 16,17 In the present research, we confirmed that the expression of lncRNA-ATB was significantly upregulated in ovarian cancer cells. Li et al found that the expression of lncRNA GAS5 was notably inhibited in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…Pancreatic cancer is one of the most aggressive malignancies worldwide, and the treatment of pancreatic cancer is extremely difficult. 19 Evidence has illustrated that miRNAs act as novel therapeutic targets in cancer, and differential miRNA expression exhibits a functional role in the progression of pancreatic cancer. 20,21 A previous study showed that miR-486 function as an oncogenic miRNA in pancreatic cancer, suggesting that miR-486 might serve as a biomarker in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable progress in the study of ceRNAs in PC. For example, lncRNA-PVT1 promotes PC cell proliferation and migration by sponging miR-448 [24]; cucurbitacin B inhibits PC cell proliferation both in vitro and in vivo through lncRNA-AFAP1-AS1 binding with miR-146b-5p [25]; and PXN-AS1 acts as a ceRNA of miR-3064, which upregulates PIP4K2B expression and suppresses the progression of pancreatic cancer [26]. In our research, subcellular fractionation assays indicated that LINC00514 was mostly located in the cytoplasm, which provided a basis for LINC00514 to act as a ceRNA in the initiation and progression of PC.…”
Section: Discussionmentioning
confidence: 99%